Effect of aqueous extract of green tea Camellia sinensis against bacteria Staphylococcus spp - Osama Bassim Al-Saffar; Ayoob Murtadha Al-Shiekh-Faqri (Journal of Madenat Alelem University College, 2015)
This study was conducted on green tea Camellia sinensis to determine the inhibition activity of plant aqueous extract against bacteria Staphylococcus spp.; The extract showed good inhibitory activity against S. aureus and S. epidermidis with 21.00 and 23.00 mm at 20 mg/mL, respectively with no significant differences with that of 10 mg/mL. The results compared to that of Ceftriaxone , Amoxicillin and Gentamicin antibiotics using agar well diffusion technique. The inhibition zone S.aureus was 10.00, 4.00, 7.00 mm for antibiotics Ceftriaxone , Amoxicillin and Gentamicin while S.epidermidis was 13.00, 5.00, 9.00 mm. The MIC results showed for the antibiotics ceftriaxone , Amoxicillin and Gentamicin which 8.00, 16.00, 5.00 and 6.00, 10.00, 3.00 mg/mL for S.aureus , S.epidermidis respectively.